The African-American woman and resistance to domination and repression: a study Alice Walker's contribution to african- american literature and thought - Makombe, Tafirenyika (Midlands State University, 2015)
This paper looks at Alice Walker's contribution to Black American writing. Her contribution is unique in the sense that she strives to highlight the condition of the African-American woman in America ñ she departs from mainstream African-American writing which focuses on the Negro's experiences in general. The paper argues that Walker presents Negro women being dominated and exploited as Negro women and not necessarily as African-Americans, and that men in general use Negro women as the arena in their power struggles. The paper acknowledges the limitations of Walker's artist vision and shows these limitations.